Formulation and Evaluation of Letrozole Nanosuspension By Probe Sonication Method using Box-behnken Design - Alekhya, Amand; Sailaja, Abbaraju K. (Current Nanomaterials, 2023)
Background: Letrozole (LTZ) is an aromatase inhibitor used to treat hormonally positive breast cancer in postmenopausal women. Letrozole is categorized as a BCS class I drug. It has poor water solubility, rapid metabolism and a range of side effects. Objective: Nanosuspension is a technique that enhances the drug's solubility and bioavailability, resulting in a faster start of the effect. The present study aimed to formulate nanosuspension using probe sonication method to enhance the solubility of Letrozole using poloxamer-188 as a stabilizer. The formulation scheme was generated using Box-Behnken design, a statistical tool for the design of experiments (DOE). Results: By employing the probe sonication method, a total of seventeen formulations were performed for letrozole nanosuspension as suggested by Box-Behnken design. The selected formulations are characterized for particle size and zeta potential. The formulations were checked on the bias percentage between the predicted and observed values and evaluated for drug content and in vitro dissolution study. The formulation was optimized using Box-Behnken design based on in vitro cumulative drug release. Among all the formulations, NS4 (500 mg poloxamer-188, 100mg Letrozole and sonication time of 20 mints) was considered best with a minimum particle size of 923.5 nm, Zeta potential value of -28.7 mV, 96.36% of drug content and 94.02% of drug release within 2 hours. Solubility was determined by the shake flask method. The solubility of the pure drug was found to be only 10%. The solubility studies performed for the optimized formulation of NS4 showed that the solubility has enhanced up to 90% compared to pure drugs. Conclusion: Thus, the present results revealed that Letrozole nanosuspension solubility has enhanced up to 90% compared to pure drugs using poloxamer-188 as a stabilizer.
Keywords: box-behnken design